PENDEKATAN SAINTIFIK TERHADAP KEMAMPUAN HOTS SISWA DI SEKOLAH DASAR - Mega Arlisyah Giri Indrati; Imas Srinana Wardani; Apri Irianto (Universitas Ahmad Dahlan, 2021)
This research is motivated by the low HOTS ability of students in elementary schools because during the learning process students are less accustomed to critical thinking, creative thinking, solving problems, and making decisions during the learning process. The application of HOTS in teaching and mentoring teachers about HOTS learning is still lacking. The aim of this research is to know the effect of the scientific approach on the HOTS ability of students in elementary schools. This study uses quantitative research with experimental and control research types. The research subjects consisted of 27 students in grade IV A and IV B 25 students at SDN Kebondalem Mojosari. The collection method uses tests. The study used the normality test, homogeneity test and t-test using the SPSS version 25 application. The results of the normality test for the experimental class (0.188) and the control class (0.156). The result of the homogeneity test is (0.668).Â From the results of the normality test and the homogeneity test, it shows that the t-test results obtained, namely the Sig (2-tailed) value is (0,000) so that the value is less than (0.05). So it can be concluded that the scientific approach has a good impact on the HOTS ability of students in elementary schools.